Redemptions and Asset Liquidations in Corporate Bond Funds - Mark Andreas Weth; Niko Dötz (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
Mutual funds' exposure to corporate bonds has brought concerns about risks arising from liquidity transformation back to the fore. With a focus on fund asset liquidity and investors, this paper explores the flow-performance relationship and the liquidity management of funds in the presence of net redemptions. We highlight the response of fund liquidity because the vulnerability to outflows is found to depend on asset liquidity and fund ownership. We construct a unique panel of German corporate bond funds by merging data on asset liquidity with information on fund ownership. First, conditional on underperformance, illiquid funds dominated by retail investors are more exposed to outflows than illiquid funds primarily owned by institutional investors. Large investors are reluctant to withdraw most likely because they internalise the fire-sale-driven loss that a withdrawal inflicts on an illiquid fund. Within institutional-oriented funds, the flow response to bad performance is only significant if fund assets are sufficiently liquid. Second, the way that fund managers liquidate their bonds to meet redemptions is found to differ across ownership structures and depends on the degree of macroeconomic uncertainty: in times of high uncertainty, managers of institutional-oriented funds sell bonds in a liquidity pecking order style, thereby preserving short-term performance. At the same time, retail-based funds do not let portfolio liquidity deteriorate - presumably to attenuate incentives for runs.
Keywords: G11; G23; G32; 330; Corporate bond funds; Ownership; Portfolio liquidity; Strategic complementarities